2008
DOI: 10.1111/j.1468-2273.2008.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary and Contextually Appropriate Approaches to Leadership of Teaching in Research‐Intensive Academic Departments in Higher Education

Abstract: This paper reports aspects of an international study of leadership of teaching in 19 departments with outstanding teaching records in 11 research-intensive universities. Leadership was found to take different forms in different discipline areas, in different organisational cultures, and in response to major problems affecting the department. While most of the heads conceived of leadership of teaching in similarly sophisticated ways, and there were other common themes across contexts, how these conceptions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 7 publications
4
67
0
6
Order By: Relevance
“…Nevertheless, like Mighty (2013), we argue that leadership in SoTL does not require an appointment to a formal position, nor does it require a particular temperament or personality type. Rather, successful leadership is situational, embedded in a context that includes many individuals' narratives and skills, disciplinary cultures, types of microcultures, as well as institutional structures, communication processes, and reward systems (Gibbs, Knapper, & Piccinin, 2008;Kezar & Eckel, 2002;Marcketti, VanDerZanden, & Leptien, 2015;. In their extensive work studying leadership and agency of change in higher education, Kezar and Lester (2011) demonstrate how successful leaders, including "bottom-up leaders," can leverage nine strategies for creating change and exerting agency: (1) intellectual opportunities, (2) professional development, (3) leveraging curricula and using classrooms as forums, (4) joining and utilizing existing networks, (5) working with students, (6) hiring like-minded people, (7) gathering data, (8) garnering resources, and (9) partnering with influential stakeholders.…”
Section: Sotl Leadership In Contextmentioning
confidence: 99%
“…Nevertheless, like Mighty (2013), we argue that leadership in SoTL does not require an appointment to a formal position, nor does it require a particular temperament or personality type. Rather, successful leadership is situational, embedded in a context that includes many individuals' narratives and skills, disciplinary cultures, types of microcultures, as well as institutional structures, communication processes, and reward systems (Gibbs, Knapper, & Piccinin, 2008;Kezar & Eckel, 2002;Marcketti, VanDerZanden, & Leptien, 2015;. In their extensive work studying leadership and agency of change in higher education, Kezar and Lester (2011) demonstrate how successful leaders, including "bottom-up leaders," can leverage nine strategies for creating change and exerting agency: (1) intellectual opportunities, (2) professional development, (3) leveraging curricula and using classrooms as forums, (4) joining and utilizing existing networks, (5) working with students, (6) hiring like-minded people, (7) gathering data, (8) garnering resources, and (9) partnering with influential stakeholders.…”
Section: Sotl Leadership In Contextmentioning
confidence: 99%
“…Apart from their need for knowledge about alternatives, of which some are suggested by amongst others, Gibbs (1992), they also need practical ways to implement the suggested strategies in the SA large class context. The resistance of colleagues towards individual lecturers, who tried out new methods, reinforces the suggestion by Gibbs et al (2008) that change should take place at departmental level. This is also why we suggest that the departmental learning culture should promote the inclusion of student-centred strategies in large classes.…”
Section: Discussionmentioning
confidence: 80%
“…Both these approaches are necessary in the large class context, therefore it is suggested that the departmental learning culture should foster the use of a variety of teaching, learning and assessment methods in large classes so that a diversity of students will be enabled to learn and to develop. Gibbs et al (2008) suggest that the academic department of research intensive universities is the appropriate place to effect change. This can be achieved by building a 'community of practice' (Wenger 1998) that involves the whole department, fosters discussion and debate about teaching and learning and where innovative teaching and assessment practices are recognised and rewarded.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Certaines universités peuvent ainsi avoir le meilleur score d'angleterre dans une de leurs composantes (« department ») et le plus faible dans une autre en dépit du fait qu'elles partagent les mêmes indicateurs de qualité. Le leadership pédagogique des départements ferait la différence, en créant des cultures qui valorisent l'enseignement, s'engagent dans un processus constant d'amélioration, créent des environnements d'apprentissage riches et attractifs, quels que soient l'environnement institutionnel et les variables prédictives (Gibbs, Knapper, & Picinnin, 2008 ;ramsden, 1998). En revanche, certaines institutions ont des « pédagogies institutionnelles » : des modèles d'enseignement et d'évaluation communs à tous les départements (oxford, Open University) qui ont tous des scores élevés au nss.…”
Section: Variations Sur Le Plan Institutionnelunclassified